Software prototyping - Nelson, Scott D.; Del Fiol, Guilherme; Hanseler, Haley; Crouch, Barbara Insley; Cummins, Mollie R. (Applied Clinical Informatics, 2016)
Health information exchange (HIE) between Poison Control Centers (PCCs) and Emergency Departments (EDs) could improve care of poisoned patients. However, PCC information systems are not designed to facilitate HIE with EDs; therefore, we are developing specialized software to support HIE within the normal workflow of the PCC using user-centered design and rapid prototyping.To describe the design of an HIE dashboard and the refinement of user requirements through rapid prototyping.Using previously elicited user requirements, we designed low-fidelity sketches of designs on paper with iterative refinement. Next, we designed an interactive high-fidelity prototype and conducted scenario-based usability tests with end users. Users were asked to think aloud while accomplishing tasks related to a case vignette. After testing, the users provided feedback and evaluated the prototype using the System Usability Scale (SUS).Survey results from three users provided useful feedback that was then incorporated into the design. After achieving a stable design, we used the prototype itself as the specification for development of the actual software. Benefits of prototyping included having 1) subject-matter experts heavily involved with the design; 2) flexibility to make rapid changes, 3) the ability to minimize software development efforts early in the design stage; 4) rapid finalization of requirements; 5) early visualization of designs; 6) and a powerful vehicle for communication of the design to the programmers. Challenges included 1) time and effort to develop the prototypes and case scenarios; 2) no simulation of system performance; 3) not having all proposed functionality available in the final product; and 4) missing needed data elements in the PCC information system.
Keywords: Software design; user-computer interface; human engineering/methods; medical informatics/methods